The Art of Dying Well according to Erasmus of Rotterdam and Teresa of Ávila - Sieruta, Dominika (Lumen et Vita, 2019)
Contemporary conversations about death and dying are lost and unsatisfying on many levels. This phenomenon subsists not only in fields like bioethics, but also in religion and spirituality. Modern culture is preoccupied with seeking ways to live a longer, youthful life, ignoring the inevitable forthcoming of death. One period during which the topic of death and dying was reflected upon by the common Christian was between the fifteenth and the seventeenth centuries, during which a specific genre of literature was formed: ars moriendi. This genre attempted to provide intellectual, cultural and religious answers as to how death should be understood and ritualized. Two spiritual writers who contributed to the understanding of ars moriendi are Desiderius Erasmus and Teresa of Ávila. What unites these figures of the Catholic tradition is their attempt to show that preparation for death is a lifelong process of cultivating appropriate virtues.